A non-invasive melanogenesis inhibition method and device / Teh Chee Kheng - Teh, Chee Kheng (2018)
Skin whitening research is an important field of cosmetic science research in Asia as bright and fair skin is preferred by Asian women. L-ascorbic acid is used in many topical cosmetic preparations since it has many favourable effects in skin, the most important being antioxidant action. L-ascorbic acid is known to both inhibiting melanin formation and reducing oxidized melanin and thus, can cause skin whitening. The percutaneous absorption of L-ascorbic acid is however limited by its impermeability and instability and the skin whitening function of L-ascorbic acid in topical cosmetic preparations is thus limited. In this present study, a transdermal iontophoresis device is fabricated to promote percutaneous absorption of L-ascorbic acid in human skin for in vivo melanogenesis inhibition and the efficacy of the transdermal iontophoresis device has been evaluated in the present study. The results indicated that the in vivo melanogenesis inhibition effect from the topical application of L-ascorbic acid is limited while the effect of topical application of L-ascorbic acid combined with the use of the invented transdermal iontophoresis device is obvious. In conclusion, the invented transdermal iontophoresis device is a safe, effective, non-invasive and cost effective portable device to promote percutaneous absorption of L-ascorbic acid in human skin for in vivo melanogenesis inhibition.